2010
DOI: 10.3109/00365540903447000
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jirovecii and cystic fibrosis in France

Abstract: We retrospectively investigated 76 patients with cystic fibrosis for the presence of Pneumocystis jirovecii, by performing real-time PCR and nested-PCR assays on 146 archival sputum specimens. P. jirovecii was detected in only 1 patient (1.3%) showing that in our region (Brest, France), the fungus is rarely involved in pulmonary colonization in patients with cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…According to our observations, it is a reliable technique that allowed us to detect Pneumocystis colonization in 12.5% of our patients. This percentage is in agreement with data reported for CF patients from European and Brazilian areas (7.4, 21.5, and 38.2%) (22,24,26) but higher than the value of 1.3% reported by Le Gal et al for a series of 76 CF patients from French Brittany (14). As previously reported (1,17), such geographic differences in Pneumocystis carriage prevalence might be linked with the local Pneumocystis circulation, which may be lower in northern France (14; our results in Lille).…”
supporting
confidence: 93%
See 3 more Smart Citations
“…According to our observations, it is a reliable technique that allowed us to detect Pneumocystis colonization in 12.5% of our patients. This percentage is in agreement with data reported for CF patients from European and Brazilian areas (7.4, 21.5, and 38.2%) (22,24,26) but higher than the value of 1.3% reported by Le Gal et al for a series of 76 CF patients from French Brittany (14). As previously reported (1,17), such geographic differences in Pneumocystis carriage prevalence might be linked with the local Pneumocystis circulation, which may be lower in northern France (14; our results in Lille).…”
supporting
confidence: 93%
“…Despite technical factors that can influence the reported prevalence of Pneumocystis colonization, and according to the abovecited studies (including our results), it appears that CF is associated with lower Pneumocystis colonization rates than are other chronic pulmonary diseases (14,20,22,24,26,27,32). Three studies have reported the association of P. jirovecii and P. aeruginosa in CF patients (14,22,25), but whether Pneumocystis infection/colonization complicated CF-associated lung disease remains unclear.…”
supporting
confidence: 46%
See 2 more Smart Citations
“…The prevalence of colonization varies with the population and the underlying disease. For example, Pneumocystis colonization is detected in individuals with cystic fibrosis, and the prevalence ranges from 1% to 22% (90,253,270). Patients with interstitial lung diseases appear to have a higher prevalence of colonization, especially if they are receiving corticosteroids.…”
Section: Colonization In Animalsmentioning
confidence: 99%